Synthesis and Pharmacological Valorization of Derivatives of 4-Phenyl-1,5-Benzodiazepin-2-One - Terence Nguema Ongone; Redouane Achour; Mostafa El Ghoul; Latifa El Ouasif; Khalid Taghzouti; Meryem El Jemli; Yahia Cherrah; Katim Alaoui; Amina Zellou (Advances in Pharmacological Sciences)
The objective of our work is to make a pharmacological study of molecules derived from 4-phenyl-1,5-benzodiazepin-2-one carrying long chains so that they have a structure similar to surfactants, with the benzodiazepine as a hydrophilic head and a carbon chain as a hydrophobic tail. First, we studied the acute toxicity of the above mentioned 4-phenyl-1,5-benzodiazepin-2-one derivatives. This study was conducted according to OECD 423 guidelines in female mice and revealed that these compounds are nontoxic. We then assessed the psychotropic effects of our products on the central nervous system (CNS). The results obtained show that 4-phenyl-1,5-benzodiazepin-2-one has no sedative effect at therapeutic doses of 100 and 200 mg/kg. On the other hand, its long-chain derivatives possess them. Moreover, all these products have no cataleptic and hypnotic effects at the doses studied. But at 100 mg/kg, these compounds all have the ability to significantly prolong the hypnotic effect of thiopental sodium.